Examining prestructured β-actin peptides as substrates of histidine methyltransferase SETD3 - Marijn N. Maas; Nurgül Bilgin; Laust Moesgaard; Jordi C. J. Hintzen; Anna Drozak; Jakub Drozak; Jacob Kongsted; Jasmin Mecinović (Scientific Reports, 2024)
Abstract The Nτ-His73 methylation of β-actin by histidine methyltransferase SETD3 is required for the integrity of the cellular cytoskeleton. Modulation of SETD3 activity in human cells facilitates cancer-like changes to the cell phenotype. SETD3 binds β-actin in an extended conformation, with a conserved bend-like motif surrounding His73. Here, we report on the catalytic specificity of SETD3 towards i, i + 3 stapled β-actin peptides possessing a limited conformational freedom surrounding the His73 substrate residue via positions Glu72 and Ile75. Stapled β-actin peptides were observed to be methylated less efficiently than the linear β-actin peptide. None of the stapled β-actin peptides efficiently inhibited the SETD3-catalyzed Nτ-His73 methylation reaction. Molecular dynamics simulations demonstrated that the unbound and SETD3-bound β-actin peptides display different backbone flexibility and bend-like conformations, highlighting their important role in substrate binding and catalysis. Overall, these findings suggest that reduced backbone flexibility of β-actin prevents the formation of optimal protein-peptide interactions between the enzyme and substrate, highlighting that the backbone flexibility needs to be considered when designing β-actin-based probes and inhibitors of biomedically important SETD3.